Performance of Flowers under Block Plantation of Poplar (Populus deltoides Bartr.) in Punjab - Dhanda, R.S.; Kaur, Navneet; Gill, R.I.S.; Singh, Baljit (Indian Journal of Agroforestry, 2020)
There is need to explore various high value crops to make the poplar based agroforestry system economically viable. Screening of various flowers under block plantation of poplar having different spacings is a step towards this direction. In this study nine flowering plants were evaluated under three years old poplar block plantation, replicated in randomized block design in North-South row direction having three different spacings (5 x 4 m, 8 x 2.5 m and 11x 3 m, diagonally paired at 2 m). No significant differences in tree height and DBH were observed among three spacings. However, the poplar trees attained maximum height (11.37 m) and DBH (15.28 cm) in 8 x 2.5 m and 5 x 4 m spacings, respectively. Different flowers such as Dimorphotheca, Gamolepis, Dianthus, Calendula, Helichrysum, Coreopsis spp., Chrysanthemum and Tagetes spp. (marigold) were grown under poplar. Dimorphotheca, Dianthus and Calendula performed significantly better in closer row spacing (5x4 m) as compared to wider row spacing (8x2.5 and 11x3 m, paired). On the other hand, growth of marigold plants was stunted under closer row spacing and significantly higher number of buds were observed in wider spacing of poplar. However, no significant effect of spacing was observed on the growth performance of Gamolepis, Helichrysum and Chrysanthemum. This preliminary study indicates that the flowering plants such as Dimorphotheca, Dianthus and Calendula require partial shade for higher seed production and can be successfully grown under block plantation of poplar.